2,3,5,4'-tetrahydroxystilbene-2-O-β-D-glucoside induces autophagy of liver by activating PI3K/Akt and Erk pathway in prediabetic rats - Xuanbin Wang; Jing Zeng; Xiao Wang; Ju Li; Jin Chen; Ning Wang; Miao Zhang; Yibin Feng; Huailan Guo (BMC, 2020)
Abstract Background 2,3,5,4'-tetrahydroxystilbene-2-O-β-D-glucoside (TSG) is an active compound derived from Polygonum multiflorum Thunb., a Chinese Taoist herbal medicine, which exerts lipid lowering, anti-cancer, anti-aging, anti-inflammatory and hepatoprotective effects. However, its role in protecting hepatocytes under pre-diabetic condition remains unclear. Methods In this study, we developed prediabetic SD rats by feeding high-fat and high-sugar diet. The body weight, blood lipid, blood glucose, and fasting insulin (FINS) and insulin resistance index (HOMA-IR) were detected and calculated to assess the potential risk of prediabetes. HE and Oil Red O staining was used, and blood level of biochemical index was detected to observe the liver injury. The autophagic cell death-associated signaling proteins, and the potential signaling factors p-Akt/Akt and p-Erk/Erk were detected using western blot to explore the potential effects of TSG on pre-diabetic liver and the underlying mechanisms. Results The results showed that the body weight in TSG-treated group was significantly decreased vs. the model group. The blood glucose, the level of FINS and HOMA-IR, TC and TG were decreased in TSG-treated group as well. Furthermore, TSG treatment significantly ameliorated lipid droplet accumulation, enhanced liver anti-oxidative response which may be associated with an increased activity of SOD and GSH-Px, and a decrease of LDLC and MDA. The autophagic cell death-associated proteins, p-AMPK, ATG12, LC3 II, and Beclin 1 were up-regulated in the TSG-treated group, while the upstream signaling pathway, PI3K/Akt and Erk, were activated. Conclusions TSG induced liver autophagic cell death to protect liver from prediabetic injury by activating PI3K/Akt and Erk. Graphical abstract